After-sales service to increase customer satisfaction: application of importance performance analysis method - Andrianto Susilo; Ridho Bramulya Ikhsan (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
This research will assess customer satisfaction with after-sale services for customers who use interior design services in Jakarta. This type of study is qualitative descriptive with survey data collection techniques—the data survey collected by cross-sectional. The data collection method uses a questionnaire distributed to 100 customers who used interior design services in Jakarta. The analytic approach used is Importance-Performance Analysis (IPA). The results of the research have successfully identified customer satisfaction with the after-sales service. There are 6 out of 20 attributes perceived as unsatisfied customers, while other attributes are perceived to be moderately satisfied and satisfied by interior design service customers in Jakarta.